Peran Pengalaman, Komitmen, Dan Perilaku Engagement Pelanggan Dalam Meningkatkan Kepuasan Pelanggan - Revin Samuel Theovani Sinaga; Sophiyanto Wuryan (Economics and Digital Business Review, 2024)
Customer satisfaction is an important aspect of any business, including the retail industry, because it directly influences the success and growth of the company, so in order to understand and improve customer satisfaction, it is important to consider the various factors that contribute to it. This research was conducted to gain a better empirical understanding of the role of customer experience, customer commitment, and customer engagement behavior in increasing customer satisfaction. Data collection was carried out by distributing questionnaires boldly to 170 respondents who were customers of clothing stores in the city of Bekasi and were aged at least 17 years and over and had experience shopping in places with a frequency of shopping at least once every 2 months. Data analysis uses Structural Equation Modeling - Partial Least Square (SEM-PLS). The research results show that customer experience can encourage customer commitment. Likewise, customer experience can increase customer satisfaction both directly and through customer commitment. Customer commitment also succeeded in improving customer behavior and customer satisfaction directly. Then, customer behavior can build customer satisfaction. Customer experience is able to directly influence customer engagement. This research shows that companies operating in the retail industry can focus on creating a good customer experience to help retain customers and create long-term relationships.